Legal Consequences For Companies That Enforce Wages Below Government Policy - Destiana, Suhendri Zikri; Suhartini, Endeh; Sihotang, Sudiman (Universitas Syiah Kuala, 2024)
Wages are a fundamental right of workers regulated by laws, including policies issued by the government regarding minimum wage. Non-compliance by companies with these policies can lead to various legal consequences, including administrative, civil, and criminal sanctions. This research discusses the legal consequences faced by companies that pay workers' wages, not by government policies, and the legal remedies available to workers when they receive wages that do not align with these policies. The research employs a normative juridical method to deeply analyse the legal consequences for companies that pay wages violating government policies. The findings indicate that companies paying wages below government standards face criminal and civil sanctions, including breaches of minimum wage laws, unlawful wage deductions, or delayed payments. Workers receiving wages that do not comply with government policies can also report to investigators or file civil lawsuits through bipartite negotiations, mediation, and the Industrial Relations Court